1992
DOI: 10.1002/pro.5560010610
|View full text |Cite
|
Sign up to set email alerts
|

A chromatographic approach to the determination of relative free energies of interaction between hydrophobic and amphiphilic amino acid side chains

Abstract: A chromatographic approach to the determination of relative free energies of interaction between hydrophobic and amphiphilic amino acid side chains AbstractA liquid chromatographic stationary phase was prepared by covalently binding to the surface of microparticulate silica gel functionality (benzylsilane), which mimics the side chain of the amino acid phenylalanine. The chromatographic retentions of the N-acetyl C-(W-methyl) amides of various hydrophobic and amphiphilic amino acids on this stationary phase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…The error estimate of k40 cal/mol associated with AAG" bind was obtained by a uniform application of the 5% relative standard deviation to all of the adsorption isotherm data. The magnitude of this error is comparable to the resolution limit of 30 caYmol reported by Pochapsky and Gopen (1992) in their chromatographic binding studies.…”
Section: Binding Isotherms For Site Identificationsupporting
confidence: 75%
See 1 more Smart Citation
“…The error estimate of k40 cal/mol associated with AAG" bind was obtained by a uniform application of the 5% relative standard deviation to all of the adsorption isotherm data. The magnitude of this error is comparable to the resolution limit of 30 caYmol reported by Pochapsky and Gopen (1992) in their chromatographic binding studies.…”
Section: Binding Isotherms For Site Identificationsupporting
confidence: 75%
“…Our development of the SIC technique was motivated by the chromatographic studies of Pochapsky and Gopen (1992) and Chiancone and co-workers (1992). Pochapsky and Gopen studied the retention of amino acid derivatives on a stationary phase covalently modified with a functional group mimicking the side chain of phenylalanine.…”
Section: Self-interaction Chromatographymentioning
confidence: 99%
“…This distinction is likely to reflect experimentally observed qualitative differences in the thermodynamics of interaction between aromatic and aliphatic sidechains. [30][31][32][33] For hydrophilic residues, which appear to the left of the reference curve, charged amino acids (K, R, E, and D) also have a s > 1.35 and can therefore be distinguished from uncharged residues (Q, P, N). Note, from the values shown in Table I or the isohysrophobicity lines in Figure 10(b), that a single hydrophobicity parameter, h s or a s h s * , is unable to distinguish not only aromatic from aliphatic residues (e.g., h F > h I > h W > h L > h Y ), but also hydrophilic charged from uncharged (e.g., h K < h Q < h R ).…”
Section: Discussionmentioning
confidence: 99%
“…The hydrophobic energy function, upon which this study is based, is no more than a lattice implementation of the physical assumption that conformational free energy of real proteins can be computed from solvent accessible surface areas of different types, such as aliphatic, aromatic and polar, combined with unit free energies of hydration, which can in principle be obtained from partition experiments (24)(25)(26)(27). Recent estimates for free energy changes involved in specific pairwise interactions obtained from HPLC experimental data are not inconsistent with this simple scheme (28,29). A recent decomposition (30) of the Miyazawa and Jerningan potential (31) has also suggested that hydrophobicity can largely explain the statistical distribution of amino acid contacts in protein structures.…”
Section: Discussionmentioning
confidence: 99%